Emergy analysis for materials selection of small hydropower station - Rifareal, Rey L. (Animo Repository, 2006)
Emergy analysis application is a new concept of energy accounting. It quantifies all the energy flows that were previously required to produce a product both the environmental and economic values data flows and are presented in a common measure, solar emergy joules (sej). Popularized by Odum, this energy accounting technique is now currently being used intensively in various areas, such as ecology, information, agriculture, energy sources and carriers, among others. This fresh methodology was applied on small hydropower station, i.e., 200-W Kaplan turbine-type hydropower and 30-kW, cross-flow turbine micro hydropower stations. A system window was drawn to delineate the process studied where in the principal materials and the connections by which they interact with each other were illustrated. Among the major processes investigated in this research include the metalcasting, metalworking, and welding processes. Local environmental values such as rainfall, solar insolation and wind data were factored in calculating/determining the emergy indicators. Transformities of various items in the study were gleaned from various databases compiled by different emergy practitioners. ii This study also employed the Multiple Attribute Decision Making (MADM) procedure to illustrate and provide sound basis in making an emergy-based material selection for small hydropower stations. Various materials such as plastic, cast iron, stainless steel, and plastic were considered in this study to determine the most environmental-friendly in the emergy perspective. Results of the completed emergy accounting on the said hydropower stations show that it causes insignificant environmental stress during its production. Notably, with its sizeable emergy yield ratio and its long-term use justifies the means by which it was manufactured vis-à-vis using oil as energy source of electricity in which the Philippines continued dependence to oil has greatly affected the country's performance both economically and environmental.